Examining the surfaces in used platinum catalysts - Trumić B.; Stanković D.; Trujić V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
For the purpose of finding more advanced platinum catalyst manufacturing technologies and achieving a higher degree of ammonia oxidation, metallographic characterization has been done on the surface of catalyst gauzes and catalyst gripper gauzes made from platinum and palladium alloys. For the examined samples of gauzes as well as the cross section of the wires, a chemical analysis was provided. The purpose of this paper is the metallographic characterization of examined alloys carried out by way of electronic microscopic scanning, X-rays as well as chemical assays which contributed greatly to a better understanding of the surface deactivation, in other words a better consideration of structural changes occurring on the wire surface.